2002
DOI: 10.1182/blood-2001-12-0276
|View full text |Cite
|
Sign up to set email alerts
|

Role of GITR in activation response of T lymphocytes

Abstract: In this study, we describe the generation and characterization of mice in which GITR gene (TNFRSF18 [tumor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
153
1
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(167 citation statements)
references
References 17 publications
8
153
1
5
Order By: Relevance
“…This was confirmed in a human T cell line (Gurney et al, 1999). Consistently, GITR-deficient mouse T cells exhibited a higher capacity to proliferate in response to TCR stimulation but underwent higher levels of activation-induced cell death (Ronchetti et al, 2002). In CD4 + CD25 + regulatory T cells, GITR signals have been shown to abrogate their suppressive function (McHugh et al, 2002;Shimizu et al, 2002).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…This was confirmed in a human T cell line (Gurney et al, 1999). Consistently, GITR-deficient mouse T cells exhibited a higher capacity to proliferate in response to TCR stimulation but underwent higher levels of activation-induced cell death (Ronchetti et al, 2002). In CD4 + CD25 + regulatory T cells, GITR signals have been shown to abrogate their suppressive function (McHugh et al, 2002;Shimizu et al, 2002).…”
Section: Introductionmentioning
confidence: 84%
“…In CD4 + CD25 + regulatory T cells, GITR signals have been shown to abrogate their suppressive function (McHugh et al, 2002;Shimizu et al, 2002). However, recent studies have demonstrated that GITR functions as a costimulatory molecule for conventional T cells in vitro (Ji et al, 2004;Kanamaru et al, 2004;Kohm et al, 2004;Muriglan et al, 2004;Ronchetti et al, 2004) and that GITR-deficient mouse CD4 + CD25 + regulatory T cells were able to exert the suppressive activity on conventional CD4 + T cells as equally as wild-type CD4 + CD25 + regulatory T cells (Ronchetti et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…4 Glucocorticoid-induced tumor necrosis factor receptor (GITR) is an emerging member of TNFRSF with crucial roles in immune regulation. 5 GITR was initially cloned from a glucocorticoid-treated T-cell hybridoma. Functional analysis demonstrated that GITR-transfected cells were more resistant to anti-CD3-induced apoptosis, compared with untransfected cells, indicating a role for GITR in the control of T-cell activation and death.…”
Section: Introductionmentioning
confidence: 99%
“…To check any aspecificities due to immunoprecipitating antibodies, lysates from GITR-myc and Siva-Xpress single transfection, immunoprecipitated with anti-Xpress or anti-myc Ab respectively, were used as negative controls. We also evaluated the level of mGITRmyc expression in comparison to that of mGITR in DEXtreated hybridoma T-cells 1 or activated T-lymphocytes 4 by semiquantitative PCR or cytofluorimetric experiments, respectively. Results indicate that similar levels of expression are detected in transfected Cos7 cells and either activated or DEX treated T-cells (data not shown).…”
mentioning
confidence: 99%